The function and regulation of heat shock transcription factor in Cryptococcus - Suo, Chenhao; Gao, Yiru; Ding, Chen; Sun, Tianshu (Frontiers in Cellular and Infection Microbiology, 2023)
Cryptococcus species are opportunistic human fungal pathogens. Survival in a hostile environment, such as the elevated body temperatures of transmitting animals and humans, is crucial for Cryptococcus infection. Numerous intriguing investigations have shown that the Hsf family of thermotolerance transcription regulators plays a crucial role in the pathogen-host axis of Cryptococcus. Although Hsf1 is known to be a master regulator of the heat shock response through the activation of gene expression of heat shock proteins (Hsps). Hsf1 and other Hsfs are multifaceted transcription regulators that regulate the expression of genes involved in protein chaperones, metabolism, cell signal transduction, and the electron transfer chain. In Saccharomyces cerevisiae, a model organism, Hsf1’s working mechanism has been intensively examined. Nonetheless, the link between Hsfs and Cryptococcus pathogenicity remains poorly understood. This review will focus on the transcriptional regulation of Hsf function in Cryptococcus, as well as potential antifungal treatments targeting Hsf proteins.